If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 = n Solving -6 = n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. -6 + -1n = n + -1n Combine like terms: n + -1n = 0 -6 + -1n = 0 Add '6' to each side of the equation. -6 + 6 + -1n = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1n = 0 + 6 -1n = 0 + 6 Combine like terms: 0 + 6 = 6 -1n = 6 Divide each side by '-1'. n = -6 Simplifying n = -6
| 4+4k=-8+k | | -300=-20p | | (4t-8)=20 | | -8n-5n=26 | | 20=-n+6n | | p=15-3Qs | | 910x-12=23 | | -13z+2=-14z+20 | | 24/4x3 | | 2(r+1)-r=-2+4 | | 103x+34=52 | | -3y+4=10 | | .87/1 | | 9/2z-7/3=41/6 | | -5-5j=-4j | | K-14=-18 | | -54=16x+312 | | 4(x+5)=3(x-11) | | (5h+2)=-8 | | 3g-8=-2+2g-10 | | 25=x-16 | | -3h+12=-7h-9-16 | | 9(x-14)=35-7(x+5) | | 24x•35y/25x | | (b+9)=2 | | 14.4=-2.7x-1.8 | | 7p-10=9p+6 | | (3z-3)=9 | | 1.4x-5.6=2.8 | | ax-ab=bx | | 5u=7+6u | | 15-x-9=21 |